2018
DOI: 10.1111/asj.12961
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inoculants and environmental temperature on fermentation quality and bacterial diversity of alfalfa silage

Abstract: To investigate the effects of inoculants and environmental temperature on fermentation quality and bacterial diversity of alfalfa silage, first-cut alfalfa was ensiled with or without two screened lactic acid bacteria (LAB) strains, Lactobacillus plantarum, LP, and Lactobacillus casei, LC. Each treatment was divided into three parts and stored at 20°C, 30°C, 40°C, respectively. After 60 days ensiling, fermentation characteristics were measured and bacterial diversity was investigated by 16S ribosomal RNA gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 54 publications
5
28
2
3
Order By: Relevance
“…The dominant strains in the alfalfa silage belong to the genera Lactobacillus, Enterococcus, Weissella, and Streptococcus in previous studies of alfalfa silage [23,24], which was a little different from the present study. The dominant three genera bacteria across the seven groups were Lactobacillus, Weissella, and Enterobater.…”
Section: Discussioncontrasting
confidence: 99%
“…The dominant strains in the alfalfa silage belong to the genera Lactobacillus, Enterococcus, Weissella, and Streptococcus in previous studies of alfalfa silage [23,24], which was a little different from the present study. The dominant three genera bacteria across the seven groups were Lactobacillus, Weissella, and Enterobater.…”
Section: Discussioncontrasting
confidence: 99%
“…This might explain the high AA concentration in CK at 90 d. A high abundance of Garciella, an anaerobic and thermophilic bacterium belonging to Clostridiales (Miranda-Tello et al, 2003), was apparent in the 90-d silage. A high abundance level of Garciella was also reported by Zhang et al (2018) in alfalfa silage ensiled at a high temperature of 40 °C. The excessively high temperature during July (with the highest temperature over 40 °C during the day time) might be one cause of Garciella growth.…”
Section: Effects Of L Plantarum On Bacterial Community Of Alfalfa Sisupporting
confidence: 59%
“…As one of the main roughages in dairy cow production, alfalfa silage can provide high-quality nutrients for livestock production. Generally, the addition of sugar sources such as molasses and fructose, added individually or mixed with other feed ingredients rich in sugar, is an effective way to increase the WSC content of alfalfa (Li et al, 2018;Muck et al, 2018;Zhang et al, 2018). It was found that pectin can be easily used by ruminants (Mertens, 2002;Liu et al, 2015), and pectin was classed as soluble and easily fermented carbohydrates based on the Cornell Net Carbohydrate and Protein System model (Sniffen et al, 1992).…”
Section: Introductionmentioning
confidence: 99%